Effect of Conservation Tillage on Earthworms in a Long-term Farm Experiment (Hungary) - Madarász, Balázs; Benke, Szabolcs (Journal of Central European Green Innovation, 2023)
Conventional ploughing tillage is associated with significant soil degradation. Erosion is increasing while soil organic matter is decreasing and life circumstances of soil biota are deteriorating. Non-inversion conservation tillage tends to provide better conditions for soil fauna due to less disturbance, more organic matter and higher soil moisture content. In our study, we investigate the effects of 18 years of conservation tillage on earthworm abundance and biomass. Our study was carried out on a 90 ha area divided into 10 pairs of plots in Southern Hungary close to Dióskál. Samples were taken in spring and autumn during the first 3 years after the shift from conventional to conservation tillage (2004–2006) and then after 15 years the sampling was repeated in the 3-year-period of 2019–2021. Samples were collected with a soil sampler of 10 cm diameter and height. Our results show that the number of earthworms increased explosively after the shift. However, their abundance do not increase after years, but their number and biomass are significantly higher in all periods of the study in conservation tillage areas.
Keywords: conservation tillage; reduced tillage; non-inversion tillage; cover crop; long-term experiment